ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Consumer Goods Industry yang Terdaftar di BEI Tahun 2018-2020) - Muhammad Rifki Gamma Putra; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of Corporate Social Responsibility disclosure on the company's financial performance as assessed from Revenue Growth, Net Profit Margin, Return on Assets, and Return on Equity.The population in this study are consumer goods industry companies listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study was selected by purposive sampling method. In this study there will be 34 companies that have met the criteria to be used as research samples. The method used in conducting the analysis is multiple linear analysis. The results of the research conducted indicate that the disclosure of Corporate Social Responsibility does not have a significant effect on Revenue Growth in the consumer goods industry companies in Indonesia. Meanwhile, the disclosure of Corporate Social Responsibility has a significant effect on Net Profit Margin, Return on Assets, and Return on Equity in consumer goods industry companies in Indonesia.